HUBUNGAN PARITAS DENGAN KEJADIAN PERDARAHAN POST PARTUM PADA IBU BERSALIN - Eka Rahayu Puji Lestari, Eka Rahayu Puji Lestari; Waqidil Hidayah, Waqidil Hidayah; Mushallinas Sholiha, Mushallinas Sholiha (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2014)
Postpartum hemorrhage is bleeding that occurs after childbirth before , during and after the discharge of the placenta . Parity is a risk hfactor that affects primary postpartum hemorrhage , the more often women experience pregnancy and childbirth the uterus so that the weaker the greater the risk of pregnancy complications . The purpose of this study was to analyze the relationsip of parity with the maternal bleeding events .Analytical survey research design with cross sectional sample of 31 respondents taken by simple random sampling technique sampling . This study was taken using interviews and observations . The data that has been collected analyzed using Spearman 's Rho test .Research shows that respondents have a safe and non- parity postpartum bleeding obtained significant p value ( 0.027 ) < ? ( 0.05 ) means that there is a relationship between the incidence of parity on maternal postpartum hemorrhage.To prevent the occurrence of post partum hemorrhage women should do with the physical preparation exercises pregnancy exercise to increase muscle strength while later childbirth . As for the risk of bleeding padaibu that high parity should be able to adjust the distance of pregnancy , so that subsequent pregnancies when the mother 's physical health has recovered . Keywords : Maternity , Parity , Post Partum Hemorrhage .